A peculiar condition: A history of the Jumping Frenchmen Syndrome in scientific and popular accounts. Issue 4 (2nd October 2018) - Richard, Mark Paul
ABSTRACT: In 1878, Dr. George Beard reported to other neurologists that in Maine there existed French-Canadian woodsmen who jumped when excited. Beard observed the phenomenon firsthand and his subsequent reports attracted the attention of Georges Gilles de la Tourette in France and other neurologists worldwide for a couple of decades. During the second half of the twentieth century, interest in the jumpers revived among neurologists, as some came forward with similar observations in different parts of Canada and the United States. This article compares and contrasts the scientific reports of the jumping syndrome with those of the popular press and highlights what they revealed about the perceived status of French-Canadian descendants.